2017
DOI: 10.1038/srep44158
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of high OPDA level correlates with reduced ROS and elevated GSH benefiting white cell survival in variegated leaves

Abstract: Variegated ‘Marble Queen’ (Epipremnum aureum) plant has white (VMW) and green (VMG) sectors within the same leaf. The white sector cells containing undifferentiated chloroplasts are viable, but the underlying mechanism for their survival and whether these white cells would use any metabolites as signal molecules to communicate with the nucleus for maintaining their viability remain unclear. We analyzed and compared phytohormone levels with their precursors produced in chloroplasts between VMW and VMG, and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 87 publications
4
17
0
Order By: Relevance
“…Our study found that chloroplasts have no intact lamellar structure in albino tissues, and that photosynthesis was suppressed. Similar results were also observed in other albino or variegated plants (Sun et al, 2017;Shih et al, 2019;Li et al, 2020). As shown in Figure 4A, four major photosynthetic complexes in plants, including PSII, PSI, the cytochrome b 6 /f (cytb 6 /f ) complex, and plastid ATP synthase, are located in the chloroplast thylakoid membrane (Rochaix, 2004).…”
Section: Photomorphogenesis Affects Chloroplast Developmentsupporting
confidence: 86%
“…Our study found that chloroplasts have no intact lamellar structure in albino tissues, and that photosynthesis was suppressed. Similar results were also observed in other albino or variegated plants (Sun et al, 2017;Shih et al, 2019;Li et al, 2020). As shown in Figure 4A, four major photosynthetic complexes in plants, including PSII, PSI, the cytochrome b 6 /f (cytb 6 /f ) complex, and plastid ATP synthase, are located in the chloroplast thylakoid membrane (Rochaix, 2004).…”
Section: Photomorphogenesis Affects Chloroplast Developmentsupporting
confidence: 86%
“…The contents of GSH and ROS were responsible for in vivo oxidative damage . Following the BIIC treatment, the serum GSH content (Figure C) was reduced, while the ROS level (Figure D) was elevated remarkably, indicating that the oxidative damage was increased upon the BIIC stimulation.…”
Section: Resultsmentioning
confidence: 96%
“…In the Arabidopsis white-green variegated mutant immutans ( im ), an inhibition of carotenoids formation was observed [38]. Similarly, the white section in leaf of variegated Epipremnum aureum contains 10-fold less carotenoids than the green section [39]. In Cyclamen purpurascens , the light green leaf stripes were found with reduced carotenoids and chlorophyll contents [40].…”
Section: Discussionmentioning
confidence: 99%